Non-viral gene therapy using multifunctional nanoparticles : status, challenges, and opportunities - Lin, Guimiao (2020)
Gene delivery for molecular-level therapeutics is regarded as a prospective remedial route to cure human diseases by the medical community. The major challenge for delivering genes in vivo is the lack of suitable delivery vehicles possessing high transfection efficiencies and low cytotoxicity. Currently, viral vectors such as retroviruses, lentiviruses, adenoviruses, adeno-associated viruses (AAV), and herpes simplex viruses (HSV) are being used as successful vectors at clinical trial levels. However, their use has raised major concerns related to insertion mutagenesis and immunogenicity in the medical research community. To address these issues, several non-viral gene delivery vectors are being explored. Among these non-viral vectors, multifunctional nanoparticles have shown superior performance in terms of enhanced gene stability, shielding of cargo from nuclease degradation, and improved passive/active targeting. This review focuses on the explicit role of various non-viral, multifunctional nanoparticles such as lipid-based nanoparticles, quantum dots (QDs), carbon nanotubes, magnetic nanoparticles, silica nanoparticles, and polymer-based nanoparticles, in distinct gene delivery strategies namely, image-guided gene delivery, optically-trackable and optically-activated gene therapy, combinational gene therapy, and present their proficiency in crossing the biological barriers. Furthermore, we highlight the applications of multifunctional nanoparticles as efficient nanovehicles in gene therapy of infectious diseases, cancers, and brain dysfunctional diseases. More importantly, we discuss the in vitro and in vivo toxicity assessments of these multifunctional nanoparticles. Summarily, we outline the present challenges that need urgent attention to translate the progress in between in vitro nanomedicine to clinical research, which may eventually lead us to advance clinical therapeutics for chronic diseases.